Networked Influence: An Introduction. (August 2019) - Jacobson, Jenna; Gruzd, Anatoliy; Kumar, Priya; Mai, Philip
We are witnessing a changing social media environment with new actors, new influencers, and new challenges. Considering the changes on social media platforms, the rise of bots, and the increased participation of state actors, this thematic collection addresses the methodological, topical, and ethical issues of networked influence. The Facebook-Cambridge Analytica scandal opened a new chapter to analyze what "influence" means in our current, complicated social media age. As discussed in the five papers stemming from the 2018 International Conference on Social Media & Society, this special issue introduces a wide array of interdisciplinary topics and approaches that highlight the rapid changes in social media environments, use, and users—with a focus on networked influence ; by doing so, we attempt to answer some of the key research questions in this area, such as (1) how to identify and measure influence (broadly defined), (2) how to track propaganda campaigns, (3) how to effectively disseminate information and measure the public's response to these information campaigns, (4) how do bots influence opinion trends on social media, and, finally, (5) how does the public frame privacy in a social media age?